2005
DOI: 10.1074/jbc.m409590200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch Stimulates Protein Kinase B/Akt Phosphorylation in Epidermal Cells via Angiotensin II Type 1 Receptor and Epidermal Growth Factor Receptor

Abstract: Mechanical stress is known to modulate fundamental events such as cell life and death. Mechanical stretch in particular has been identified as a positive regulator of proliferation in skin keratinocytes and other cell systems. In the present study it was investigated whether antiapoptotic signaling is also stimulated by mechanical stretch. It was demonstrated that mechanical stretch rapidly induced the phosphorylation of the proto-onco- The application of mechanical forces is a ubiquitous challenge to skin cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 42 publications
(29 reference statements)
6
65
0
Order By: Relevance
“…Stretch-induced activation of the AT 1 receptor protects cells against induced apoptosis involving PKB/Akt signaling (Kippenberger et al, 2005). Mechanical stretch potentiates AngII-induced VSMCs proliferation in spontaneously hypertensive rat through an AT 1 receptor/ EGFR/ERK-dependent pathway.…”
Section: E Signalingmentioning
confidence: 99%
“…Stretch-induced activation of the AT 1 receptor protects cells against induced apoptosis involving PKB/Akt signaling (Kippenberger et al, 2005). Mechanical stretch potentiates AngII-induced VSMCs proliferation in spontaneously hypertensive rat through an AT 1 receptor/ EGFR/ERK-dependent pathway.…”
Section: E Signalingmentioning
confidence: 99%
“…We focused our studies on EGFR-activated signaling, as it regulates downstream effector pathways (e.g., PI3K and MAP kinases) that activate various transcription factors in response to specific stimuli (26,27). Furthermore, several studies have shown that EGFR acts as a biosensor to transduce signals from mechanical forces in various cell types, including pulmonary epithelial cells (28)(29)(30)(31)(32)(33). To determine whether this receptor-activated signaling modulates CS-induced Nrf2-ARE activation, CS-stimulated ARE-Luc activity was analyzed in the presence or absence of AG1478, a pharmacologic agent that specifically blocks EGFR tyrosine kinase activity.…”
Section: Egfr-activated Signaling Is Essential For Cs-induced Nrf2/ Amentioning
confidence: 99%
“…In a similar study, EGFR was found to be involved in cyclic stretch activation of ERK1/2, although Ras was not implicated (17). The mechanoactivated nature of RTKs has been observed in other tissues as well: Mechanical stretch activates EGFR in keratinocytes (18), stimulates proliferation of vascular smooth muscle cells via the insulin-like growth factor receptor (19), and activates the EGFR (20) and the PDGFR (21,22), with the latter implicated in mechanical strain-induced embryonic stem cell differentiation into vascular smooth muscle cells (23). In this study, we focused on whether the receptor tyrosine kinases EGFR, FGFR, and PDGFR play roles in the proximal mechanotransduction response of human lung fibroblasts to tonic stretch.…”
mentioning
confidence: 73%